A Randomized Control Trial Comparing Combined Glandular Lidocaine Injection and Intraurethral Lidocaine Gel with Intraurethral Lidocaine Gel Alone in Cystoscopy and Urethral Dilatation - Gooran, Shahram; Pourfakhr, Pejman; Bahrami, Shirin; Fakhr Yasseri, Ali Mohammad; Javid, Amir; Behtash, Negar; Pourmand, Gholamreza (Urology Journal, 2017)
Purpose: Cystoscopy is one of the most common urologic procedures. The aim of this study is to investigate the combined effect of intraurethral lidocaine gel and intraglandular injection of lidocaine 2% on pain during and after cystoscopy. Materials & Methods: In this double-blind, parallel group randomized clinical trial, 156 patients referred for double J removal, urethral dilatation, or cystoscopy were enrolled. The patients were divided into two groups, A and B. All patients received 20 cc of intraurethral lidocaine gel 2%. In group A (N = 75), lidocaine 2% was also injected into the glans penis. The patients in group B (N = 81) only received the intraurethral lidocaine gel. Cystoscopy was performed 10 minutes later. The primary outcome of interest was measured in terms of pain score (visual analogue scale) during and 5 minutes after cystoscopy. Results: Immediate pain score after the procedure was 3.4 ± 3 and 4.6 ± 3 in groups A and B, respectively (P = .011). Conclusion: Based on the findings of the present study, lidocaine injection into the glans penis significantly reduced pain perception.